Evaluation of the Attitudes and Depression Levels of Families Who Apply to AMATEM Due to Substance Use Disorder Toward the Addicted Member - Yılmaz Tuncel, Gözde; Şaşman Kaylı, Derya; Cengisiz, Cengiz; Özyurt, Beyhan Cengiz; Gürpınar Çavuşoğlu, Tuğba; Deveci, Artuner (Addicta: The Turkish Journal on Addictions, 2025)
The aim of this cross-sectional study is to determine the depression levels of family members of individuals with substance use disorders and their attitudes toward the addicted member, and to examine the relationship between them. The sample of the research consists of 106 family members of individuals with substance use disorder who applied to Manisa Amatem between 21 March 2022 and 20 September 2022 and agreed to participate in the research. Sociodemographic questionnaire, Family Addiction Profile Index Scale (BAPI-A) and Beck Depression Scale were used as data collection tools in the study. It was found that 47% of the family members of individuals with substance use disorder had moderate depression symptoms and 20% of them had mild depression symptoms. It was determined that as the participants’ depression levels increased, problems in family relationships, problems in parenting skills, and problems in attitude toward the addicted member also increased. It has been found the depression level was higher in women, the parenting skills of the mothers were more inadequate. This research is important as it shows that substance addicted individuals need psychotherapeutic intervention, rehabilitation programs, psychoeducation, and psychosocial support regarding the addiction process, tailored to the needs of their family members.